Heat islands in cities in the interior of the state of são paulo, brazil - Porangaba, Gislene Figueiredo Ortiz; De Costa Trindade Amorim, Margarete Cristiane [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
The quality of urban environments has proven inappropriate for a significant portion of the population due to a failure to consider, in their territorial expansion process, the physical characteristics of these environments. In order to mitigate issues related to the quality of these environments, particularly regarding characteristics of temperature and generation of surface heat islands, the scientific community has developed analysis methods to assist in the environmental planning of cities, using remote sensing as a key ally. In the analysis of surface heat islands, remote sensing assists in the representation of the temperature of urban targets in relation to the near surroundings and the assessment of the vegetation, which is a key element to mitigate surface heat islands. In this sense, this paper aims to analyze the vegetation cover using the Normalized Difference Vegetation Index (NDVI) and its interference on surface temperature in the cities of Assis, Cândido Mota, Maracaí and Tarumã (São Paulo, Brazil). To do that, we used images from the Landsat 8 satellite, band 10, to calculate the temperature of the targets, and bands 4 and 5, to calculate the NDVI. It can be concluded through the NDVI analysis that the exuberant and/or active vegetation (high NDVI) plays a key role in reducing temperatures in the targets. On the other hand, a low NDVI, due to the high building density in urban areas or the dry season, particularly in nearby rural areas, favors surface heating.
Geotecnologias Aplicadas à Análise de Ilhas de Calor de Superfície em Cidades do Interior do Estado de São Paulo
Keywords: NDVI; Remote sensing; Surface temperature; Urban climate